The Protection of Lactiplantibacillus plantarum CCFM8661 Against Benzopyrene-Induced Toxicity via Regulation of the Gut Microbiota - Yu, Leilei; Zhang, Lingyu; Duan, Hui; Zhao, Ruohan; Xiao, Yue; Guo, Min; Zhao, Jianxin; Zhang, Hao; Chen, Wei; Tian, Fengwei (Frontiers in Immunology, 2021)
The present study evaluated the protection of Latilactobacillus plantarum CCFM8661, a candidate probiotic with excellent benzopyrene (B[a]P)-binding capacity in vitro, against B[a]P-induced toxicity in the colon and brain of mice. Each mouse in the L. plantarum treatment groups were administered 2 × 109 colony forming unit (CFU) of L. plantarum strains once daily, followed by an oral dose of B[a]P at 50 mg/kg body weight. Mice that received B[a]P alone served as the model group. Behavior, biochemical indicators in the colon and brain tissue, and the microbiota composition and short-chain fatty acid (SCFA) levels in the gut were investigated. Compared to the treatment in the model group, CCFM8661 treatment effectively reduced oxidative stress in the brain, improved behavioral performance, increased intestinal barrier integrity, and alleviated histopathological changes in mice. Moreover, CCFM8661 increased the gut microbiota diversity and abundance of Ruminococcus and Lachnospiraceae and reduced the abundance of pro-inflammatory Turicibacter spp. Additionally, the production of SCFAs was significantly increased by L. plantarum CCFM8661. Our results suggest that CCFM8661 is effective against acute B[a]P-induced toxicity in mice and that it can be considered as an effective and easy dietary intervention against B[a]P toxicity.